Respuesta :
Answer:
nine to the one third power all raised to the third power equals nine raised to the one third times three power equals nine
Step-by-step explanation:
we know that
The Power of a Power Property , states that :To find a power of a power, multiply the exponents
so
[tex](a^{b})^{c}=a^{b*c}[/tex]
In this problem we have
[tex]9^{\frac{1}{3}} =\sqrt[3]{9}[/tex]
Remember that
[tex]\sqrt[3]{9}=9^{\frac{1}{3}}[/tex]
Raise to the third power
[tex][9^{\frac{1}{3}}]^3[/tex]
Applying the power of power property
[tex]9^{\frac{3}{3}}[/tex]
[tex]9^{1}[/tex]
[tex]9[/tex]
therefore
nine to the one third power all raised to the third power equals nine raised to the one third times three power equals nine
Answer:
Option 1.
Step-by-step explanation:
The given equation is
[tex]9^{\frac{1}{3}}=\sqrt[3]{9}[/tex]
We need to find the equation which justifies the given equation.
Taking cube on both sides.
[tex](9^{\frac{1}{3}})^3=(\sqrt[3]{9})^3[/tex]
[tex](9^{\frac{1}{3}})^3=9[/tex]
Taking LHS,
[tex]LHS=(9^{\frac{1}{3}})^3[/tex]
Using power property of exponents.
[tex]LHS=9^{\frac{1}{3}\times 3}[/tex] [tex][\because (a^m)^n=a^{mn}][/tex]
[tex]LHS=9^{\frac{3}{3}}[/tex]
[tex]LHS=9^{1}[/tex]
[tex]LHS=9[/tex]
[tex]LHS=RHS[/tex]
The required equation is
[tex](9^{\frac{1}{3}})^3=9^{\frac{1}{3}\times 3}=9[/tex]
"Nine to the one third power all raised to the third power equals nine raised to the one third times three power equals nine".
Therefore, the correct option is 1.